441 Understanding the unintended consequences of new healthcare technologies aimed at supporting patient safety: a qualitative study. (13th April 2023) - Abdelaziz, S; Garfield, S; McLeod, M; Norton, J; Lloyd, J; Wheeler, C; Neves, A L; van Dael, J; Franklin, B D
Abstract: Introduction: Technologies such as electronic prescribing, clinical decision support systems, and electronic medication dispensers, are increasingly being introduced into healthcare. Existing toolkits focus on the implementation of such technologies, rather than identifying and mitigating any unintended consequences technologies may have on patient safety. They also focus on high-level organisational issues instead of those faced by end-users: frontline staff, patients and carers. Aim: To identify and classify types of unintended consequences that may be encountered by technologies' end-users, in order to inform development of a tool for identifying and preventing technology-related risks on patient safety. Methods: Five focus group discussions with healthcare professionals, patients and carers were conducted through video-conferencing. Healthcare professionals with experience of using/implementing healthcare technologies and known to the research team via professional networks were invited to participate. Patient/carer participants were recruited using convenience sampling via an external research-participant organisation. Participants were asked to identify patient safety risks associated with the use of healthcare technologies, drawn from their own experiences and through consideration of hypothetical risks. Discussions were audio-recorded and transcribed verbatim. Transcripts were analysed by two researchers (NVivo R1.6) and two public partners (manually), using iterative inductive thematic analysis. Results: Eleven healthcare professionals and 29 patients and carers participated in focus groups. Three focus groups comprised patients, carers, and healthcare professionals. Two involved solely patients and carers. Analysis revealed five areas of unintended consequences (Table 1). Most unintended consequences identified by patients and carers were similar to those described by healthcare professionals. Healthcare professionals also described additional unintended consequences associated with technologies designed specifically for their use. Conclusion: A limitation of the study is that many of the unintended consequences identified related to virtual health technologies used during the COVID-19 pandemic, which may affect generalisability. A strength is that unintended consequences that have been overlooked in existing literature, such as the build-up of patients' psychological dependence on technologies, were identified. Developing a tool based on these will allow implementers and users of healthcare technologies to consider such issues and address the potential risks they may have on patient safety before healthcare technologies are fully implemented in practice.